COVID-19. A Catechetical-Experiential Reading - Carl-Mario Sultana (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2020)
This article seeks to give a Christian understanding to the reality of COVID-19 which the world has gone through in the past months. This is done in a catechetical way by elaborating upon what truly transforms a lived event into an experience and into a Christian religious experience through a catechetical process. This implies seeking to understand any lived event by reflecting upon it and then applying the results of one’s reflection to one’s life. This theoretical framework is then applied to the reality of COVID-19 with the aim of rendering the lived event of the pandemic into a Christian religious experience which leaves a positive effect on the lives of believers through a catechetical process of understanding it in the light of the Word of God, and then applying the outcomes to one’s life afterwards.